Platelets Toll‐like receptor‐4 in Crohns disease. (29th December 2016) - Schmid, Werner; Novacek, Gottfried; Vogelsang, Harald; Papay, Pavol; Primas, Christian; Eser, Alexander; Panzer, Simon
Abstract: Background: Platelets are activated in Crohn's disease (CD) and interplay with leukocytes. Engagement of Toll‐like receptor‐4 (TLR‐4), which is expressed in human platelets, may be involved in crosstalks between platelets and leukocytes leading to their mutual activation for host defense. Materials and methods: Human neutrophil peptides (HNPs), lipoprotein binding peptides, and sCD14 were determined by enzyme‐linked immunosorbent assays in 42 patients with active CD, in 43 patients with CD in remission, and in 30 healthy individuals. Neutrophil‐platelet aggregates and binding of the TLR‐4 monoclonal antibody to platelets were determined by flow cytometry. Results: Levels of HNPs were higher in patients with CD than in controls ( P = 0.0003 vs. active CD and P = 0.01 vs. CD in remission). Likewise, neutrophils with adhering platelets were higher in patients with active CD than in controls ( P = 0.004). Binding of the TLR‐4 antibody in patients with active CD was similar to that in controls, while patients in remission had significantly higher binding capacities ( P = 0.59 and P = 0.003). Incubation of plasma from patients with active disease or patients in remission with platelets from healthy controls confirmed lower binding of the TLR‐4 antibody in the presence of plasma from active diseased patients compared to controls ( P = 0.039), possibly due to high levels of lipopolysaccharides, as suggested by high levels of sCD14 and lipoprotein binding protein. Conclusion: Our study indicates involvement of platelet TLR‐4 in enhancing the secretion of antimicrobial peptides from neutrophils. While platelet aggregation can be due to a variety of mechanisms in inflammatory disease, the mutual activation of platelets and neutrophils may augment host defense.